ANALISIS KEPEMIMPINAN, MOTIVASI, DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN AL IKHLAS STATIONERY SOLO - Yahya Hari Anggoro; Djumali Djumali; Ida Aryati (JURNAL ILMIAH EDUNOMIKA, 2020)
Creating high employee performance for company development requires the success of an organization that is affected by the performance of its employees. Employees are the most important and most influential factor in the ongoing activities of a company. With the company's goals the company will run well. This study aims to determine the effect of leadership, motivation and workload on the performance of Al Ikhlas Stationery Solo employees. This research uses quantitative descriptive methods. The questionnaire was used to obtain data from Al Ikhlas Stationery employees using 55 respondents and took approximately 3 months in the study. The results showed that the variables of leadership, motivation, and workload had a positive and significant effect on the performance of Al Ikhlas Stationery Solo employees. Keywords: Leadership, Motivation, Workload, Employee Performance